The Effect of Training, Competence and Compensation on the Peformance of New Civil Servants with Organizational Culture as Intervening: Studies at the Ministry of Health of the Republic of Indonesia - Edi Sugiono; Suryono Efendi; Yani Afrina (International Journal of Science and Society, 2021)
The Coronavirus pandemic is a severe problem throughout 2020 for the whole world, including Indonesia. The Coronavirus pandemic question is not only about the virus, which makes the health of an individual decrease, but in several countries, including Indonesia, the existence of the coronavirus pandemic has put the health ministry's performance in the spotlight because the coronavirus pandemic is related to health. Many have speculated that the increasing coronavirus pandemic in Indonesia is due to the Ministry of Health's slow performance in preventing the Coronavirus pandemic. This research uses quantitative methods with a descriptive analysis approach. The questionnaire uses a closed questionnaire presented in a question or statement equipped with alternative responses/answers. This research's analysis method is the quantitative analysis method using Structural Equation Model (SEM). This study shows that training is proven to have a positive and real effect on the Ministry of Health's organizational culture, meaning that the Ministry of Health's increasing practice will improve the Ministry of Health employees' corporate culture. This influence is determined by the training held by BBPK Jakarta for employees of the Ministry of Health to form employees with an excellent organizational culture.